Herbicide resistance in China: a quantitative review. Issue 6 (23rd August 2019) - Liu, Xiangying; Xiang, Shihai; Zong, Tao; Ma, Guolan; Wu, Lamei; Liu, Kailin; Zhou, Xuguo; Bai, Lianyang
Abstract: The widespread, rapid evolution of herbicide-resistant weeds is a serious and escalating agronomic problem worldwide. During China's economic boom, the country became one of the most important herbicide producers and consumers in the world, and herbicide resistance has dramatically increased in the past decade and has become a serious threat to agriculture. Here, following an evidence-based PRISMA (preferred reporting items for systematic reviews and meta-analyses) approach, we carried out a systematic review to quantitatively assess herbicide resistance in China. Multiple weed species, including 26, 18, 11, 9, 5, 5, 4, and 3 species in rice ( Oryza sativa L.), wheat ( Triticum aestivum L.), soybean [ Glycine max (L.) Merr.], corn ( Zea mays L.), canola ( Brassica napus L.), cotton ( Gossypium hirsutum L.)., orchards, and peanut ( Arachis hypogaea L.) fields, respectively, have developed herbicide resistance. Acetolactate synthase inhibitors, acetyl-CoA carboxylase inhibitors, and synthetic auxin herbicides are the most resistance-prone herbicides and are the most frequently used mechanisms of action, followed by 5-enolpyruvylshikimate-3-phosphate synthase inhibitors and protoporphyrinogen oxidase inhibitors. The lack of alternative herbicides to manage weeds that exhibit cross-resistance or multiple resistance (or both) is an emerging issue and poses one of the greatest threats challenging the crop production and food safety both in China and globally.